Proposal for a Hybrid Cycloconverter with Three-phase Input and Single-phase Output with Low Output Voltage Harmonic Distortion - Guimarães, Érico C.; Freitas, Pedro A. R.; Melo, Fernando C.; Lima, Gustavo B.; Freitas, Luiz C.; Freitas, Luiz C. G. (Eletrônica de Potência, 2024)
This paper presents a proposal for a Hybrid Cycloconverter with Three-phase Input and Single-phase Output with Low Output Voltage Harmonic Distortion (THDV). The proposed topology is based on the series association of Thyristor-based Cycloconverter with a non-isolated two DC-DC converters. The DC-DC converters are designed to process the minimum amount of energy necessary to mitigate harmonic distortion of the output voltage and, hence, to increase power density and efficiency. Theoretical analysis is presented and corroborated by experimental results obtained with a small-scale laboratory prototype. Different operating modes are analyzed and confirm the functionality of the proposed converter.